PENAMBAHAN GULA DAPAT MENINGKATKAN STABILITAS WARNA EKSTRAK ANTOSIANIN BUAH MURBEI HITAM YANG TERPAPAR CAHAYA FLUORESENS - Erlien Giovani Soeroso; Lydia Ninan Lestario; Yohanes Martono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2017)
Anthocyanins are red to purple pigments and one of potent safe and natural food colorants which possess superior antioxidant activity. However, the stability of anthocyanins depends on various factors, including structure and concentrations, pH, temperatures, light, co-pigment, ascorbic acid, enzymes, metal ions, sugars, protein, sulfur dioxide. The aims of this research were to evaluate the effects of sugar addition on the stability of anthocyanin of black mulberry under different fluorescent light intensities and to determine the appropriate concentration of sugar that could increase black mulberry (Morus nigra L.) anthocyanin stability. Fluorescent lamp at 3370, 4210, and 8820 lux (18, 23, and 32 watt, respectively) were used to illuminate black mulberry fruit extract (10.09 g/L) following 20, 40, 60% (w/v) of sugar addition. Determination of anthocyanin color stability in extract of black mulberry fruit was perfomed using degradation kinetics modeling to obtain the appropriate order. The concentration rate (k) and half life (t1/2) were then calculated based on subsequent order. The results showed that 20% sugar addition enhance the stability of black mulberry anthocyanin extract as compared to that of control (without sugar addition) as indicated by half life increment from 170.826 to 183.733 h. On the other hand, anthocyanin stability decreased to 166.618 and 146.235 h half life with further sugar addition to 40 and 60%, respectively. Therefore, 20% sugar addition to black mulberry extract could improve its anthocyanin stability.